Systemic Autoimmune Disease Among Adults Exposed to the September 11, 2001 Terrorist Attack. Issue 5 (1st April 2020) - Miller‐Archie, Sara A.; Izmirly, Peter M.; Berman, Jessica R.; Brite, Jennifer; Walker, Deborah J.; Dasilva, Renato C.; Petrsoric, Lysa J.; Cone, James E.
Abstract : Objective: Autoimmune disease is an emerging condition among persons exposed to the September 11, 2001 attack on the World Trade Center (WTC). Components of the dust cloud resulting from the collapse of the WTC have been associated with development of a systemic autoimmune disease, as has posttraumatic stress disorder (PTSD). We undertook this study to determine whether dust exposure and PTSD were associated with an increased risk of systemic autoimmune disease in a 9/11‐exposed cohort. Methods: Among 43, 133 WTC Health Registry enrollees, 2, 786 self‐reported having a post‐9/11 systemic autoimmune disease. We obtained informed consent to review medical records to validate systemic autoimmune disease diagnoses for 1, 041 enrollees. Diagnoses of systemic autoimmune diseases were confirmed by classification criteria, rheumatologist diagnosis, or having been prescribed systemic autoimmune disease medication. Controls were enrollees who denied having an autoimmune disease diagnosis (n = 37, 017). We used multivariable log‐binomial regression to examine the association between multiple 9/11 exposures and risk of post‐9/11 systemic autoimmune disease, stratifying by responders (rescue, recovery, and clean‐up workers) and community members (e.g., residents, area workers). Results: We identified 118 persons with systemic autoimmune disease. Rheumatoid arthritis was most frequent (n = 71), followed by Sjӧgren's syndrome (n = 22), systemic lupus erythematosus (n = 20), myositis (n = 9), mixed connective tissue disease (n = 7), and scleroderma (n = 4). Among 9/11 responders, those with intense dust cloud exposure had almost twice the risk of systemic autoimmune disease (adjusted risk ratio 1.86 [95% confidence interval 1.02–3.40]). Community members with PTSD had a nearly 3‐fold increased risk of systemic autoimmune disease. Conclusion: Intense dust cloud exposure among responders and PTSD among community members were associated with a statistically significant increased risk of new‐onset systemic autoimmune disease. Clinicians treating 9/11 survivors should be aware of the potential increased risk of systemic autoimmune disease in this population.